2016
DOI: 10.1007/s10555-016-9615-3
|View full text |Cite
|
Sign up to set email alerts
|

The promising alliance of anti-cancer electrochemotherapy with immunotherapy

Abstract: Anti-tumor electrochemotherapy, which consists in increasing anti-cancer drug uptake by means of electroporation, is now implanted in about 140 cancer treatment centers in Europe. Its use is supported by the English National Institute for Health and Care Excellence for the palliative treatment of skin metastases, and about 13,000 cancer patients were treated by this technology by the end of 2015. Efforts are now focused on turning this local anti-tumor treatment into a systemic one. Electrogenetherapy, that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 83 publications
(116 reference statements)
1
94
0
4
Order By: Relevance
“…Interestingly preliminary data sustain the use of ECT in association with systemic immune checkpoint inhibitors, such as anticytotoxic T lymphocyte-associated antigen-4 or antiprogrammed cell death protein 1 antibodies. The combined concept of local therapy with systemic immune checkpoint inhibition is currently being studied in prospective clinical trials and has the potential to further improve the success of cancer immunotherapy 35,36…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly preliminary data sustain the use of ECT in association with systemic immune checkpoint inhibitors, such as anticytotoxic T lymphocyte-associated antigen-4 or antiprogrammed cell death protein 1 antibodies. The combined concept of local therapy with systemic immune checkpoint inhibition is currently being studied in prospective clinical trials and has the potential to further improve the success of cancer immunotherapy 35,36…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative, the efficacy of IL‐12 therapy could be enhanced by combining it with metronomic cyclophosphamide to selectively decrease the amount of Tregs, as IL‐12 effects are transient and induce a rebound in Tregs . Furthermore, immunotherapy generally has a more powerful effect in a minimal residual disease setting, thus, IL‐12 therapy could benefit from a combinatorial strategy with surgery or electrochemotherapy …”
Section: Discussionmentioning
confidence: 99%
“…The first randomized clinical trial in humans with cutaneous metastases treated with CaEP or ECT using bleomycin, showed similar results between both techniques [8]. However, seems that tumor cells are more sensitive to bleomycin than normal ones [2]. Thus, need to be conducted to better understand the complex mechanism behind the CaEP [3][4][5][6][7] A previous study compared the use of bleomycin with calcium compounds as calcium chloride and calcium glubionate [5].…”
Section: Discussionmentioning
confidence: 99%